An 8‐element Tx/Rx array utilizing MEMS detuning combined with 6 Rx loops for 19F and 1H lung imaging at 1.5T. Issue 4 (12th April 2020) - Maunder, Adam; Rao, Madhwesha; Robb, Fraser; Wild, Jim M.
Abstract : Purpose: To firstly improve the attainable image SNR of 19 F and 1 H C3 F8 lung imaging at 1.5 tesla using an 8‐element transmit/receive (Tx/Rx) flexible vest array combined with a 6‐element Rx‐only array, and to secondly evaluate microelectromechanical systems for switching the array elements between the 2 resonant frequencies. Methods: The Tx efficiency and homogeneity of the 8‐element array were measured and simulated for 1 H imaging in a cylindrical phantom and then evaluated for in vivo 19 F/ 1 H imaging. The added improvement provided by the 6‐element Rx‐only array was quantified through simulation and measurement and compared to the ultimate SNR. It was verified through the measurement of isolation that microelectromechanical systems switches provided broadband isolation of Tx/Rx circuitry such that the 19 F tuned Tx/Rx array could be effectively used for both 19 F and 1 H nuclei. Results: For 1 H imaging, the measured Tx efficiency/homogeneity (mean ± percent SD; 6.79 μ T / kW ± 26 % ) was comparable to that simulated ( 7.57 μ T / kW ± 20 % ). The 6 additional Rx‐only loops increased the mean Rx sensitivity when compared to the 8‐element array by a factor of 1.41× and 1.45× in simulation and measurement, respectively. In regions central to the thorax, the simulated SNR of the 14‐element array achieves ≥70% of the ultimate SNR when including noise from the matching circuits and preamplifiers. A measured microelectromechanical systems switching speed of 12 µs and added minimum 22 dB of isolation between Tx and Rx were sufficient for Tx/Rx switching in this application. Conclusion: The described single‐tuned array driven at 19 F and 1 H, utilizing microelectromechanical systems technology, provides excellent results for 19 F and 1 H dual‐nuclear lung ventilation imaging.